« Communistes, aux armes ! » : les unités à destination spéciale (TchON) au sortir de la guerre civile en Ukraine (1920-1924) - Éric Aunoble (Amnis)
Based upon Ukrainian archives, the article examines the Special Purpose Units (Chasti osobogo naznacheniya, CHON, 1919-1924), which are armed detachments composed of communist activists. To counteract the perils of the Civil War, the Bolshevik power creates different types of armed units, which differs by their specific mission (protection, control, repression...) and their institutional affiliation (army, secret police, Party). Although they were set up by the Communist Party, the central institution of the new regime, the Chon should struggle to get a place. Many communist leaders who were keen on military or police activity were already absorbed by the Red Army or the Cheka. In addition, the non-permanent nature of these auxiliary forces affects their durability and visibility. With the set up of a permanent high staff to address this problem, Chon lose much of their original operational character of party militia. But they preserve their symbolic importance: being a "communard", e.g. a member of Special purpose units, is being a member of the community in power. Straddling two periods, the Civil war and the "peaceful construction", these units belong to both the military field and to the political field and give an insight of the relationships of the CP and its activists with the questions of violence and power.